Autophagy of bovine mammary epithelial cell induced by intracellular Staphylococcus aureus - Geng, Na; Liu, Kangping; Lu, Jianwei; Xu, Yuliang; Wang, Xiaozhou; Wang, Run; Liu, Jianzhu; Liu, Yongxia; Han, Bo (The journal of microbiology, 2020)
Bovine mastitis is a common disease in the dairy industry that causes great economic losses. As the primary pathogen of contagious mastitis, Staphylococcus aureus ( S. aureus ) can invade bovine mammary epithelial cells, thus evading immune defenses and resulting in persistent infection. Recently, autophagy has been considered an important mechanism for host cells to clear intracellular pathogens. In the current study, autophagy caused by S. aureus was detected, and the correlation between autophagy and intracellular S. aureus survival was assessed. First, a model of intracellular S. aureus infection was established. Then, the autophagy of MAC-T cells was evaluated by confocal microscopy and western blot. Moreover, the activation of the PI3K-Akt-mTOR and ERK1/2 signaling pathways was determined by western blot. Finally, the relationship between intracellular bacteria and autophagy was analyzed by using autophagy regulators (3-methyladenine [3-MA], rapamycin [Rapa] and chloroquine [CQ]). The results showed that S. aureus caused obvious induction of autophagosome formation, transformation of LC3I/II, and degradation of p62/SQSTM1 in MAC-T cells; furthermore, the PI3K-Akt-mTOR and ERK1/2 signaling pathways were activated. The number of intracellular S. aureus increased significantly with autophagy activation by rapamycin, whereas the number decreased when the autophagy flux was inhibited by chloroquine. Therefore, this study indicated that intracellular S. aureus can induce autophagy and utilize it to survive in bovine mammary epithelial cells.